Três questões sobre a arte contemporânea - Rachel Cecília de Oliveira Costa (2014)
This thesis is based on three questions about art that are commonplaces, and precisely because they seem obvious, are often overlooked. The questions point and call into discussion the changes that occurred in art world in the last century that resulted in what is known today as contemporary art. They are, respectively, the questioning of technical skill, the dematerialization of the object and the questioning of aesthetic experience. The analysis of the issues raised by each of them is carried out by two different points of view, the Arthur Dantos and the Vilém Flussers. With the election of the most fruitful solutions of each, a conclusion is drawn from the proposition that everything can become art. The intent is to propose a way of understanding the world of contemporary art, without forgetting that the plurality characteristic of artistic manifestations should be also part of its philosophy. Therefore, this thesis starts from the realization of pluralism and presents a reading that emphasizes its benefits and contributions to the way of making and experiencing art today.